Advantages and disadvantages of the use of Artificial Intelligence in the public policy-cycle: analysis of international cases - Arguelles Toache, Eugenio (Acta Universitaria, 2023)
In the last decade there has been an increasing use of Artificial Intelligence (AI) in public administration; however, the scientific study of this subject is relatively incipient since the statements about its advantages and disadvantages are based on assumptions and predictions of researchers and lack sufficient empirical evidence. The objective of this work is to analyze the advantages and disadvantages of the use of AI in the public policy-cycle to contribute to solving this gap. To this end, a comparative study of eight international cases is carried out. The analysis shows that the main advantage of using AI is that it allows processing and analyzing a large amount and diversity of information immediately to automate various processes within the public policy-cycle; however, there are disadvantages such as exclusion, biases in estimates, lack of privacy, and lack of transparency.